Women's Collective Action for Empowerment in Indonesia - Lockley, Anne; Marcoes, Lies; Nugroho, Kharisma; Boang-Manalu, Abby Gina (Yayasan Jurnal Perempuan, 2019)
Women’s collective action has been used by women’s group in Indonesia since early 20th century. The collective action of women in this study is defined as the formal or informal formation and activity of goups or networks of predominantly women that aim to bring about positive changes in women’s lives. Eight case studies of women’s collective actions discussed in this study reveal variety of backgrounds, motives and agencies in those collective actions. This variety exist due to the different and specific conditions and needs of each of the women’s groups. The object of the study in this research were eight collective actions, namely: Balai Sakinah ‘Aisyiyah (BSA), Serikat Perempuan Kepala Keluarga (PEKKA), Sekolah Perempuan, Koalisi Perempuan Indonesia Parepare branch, MUIWO, Kelompok Bunda Kreatif, Community Center, and Posko Lestari and Posko Mentari. The data of the research were collected through document review, surveys, and in-depth interviews. This research finds that the involvement of women in collective actions stem from gender inequality that they experience in their daily lives. Through the collective actions the women were empowered to strengthen their access to social services and legal protection. This research also finds there were growing understanding about the concept of gender inequality among the women who involved in the collective actions.